PERAN ATASE KETENAGAKERJAAN DALAM PELINDUNGAN PEKERJA RUMAH TANGGA (PRT) INDONESIA DI MALAYSIA PERIODE 2013-2018 - Fatimah Nudhya Hanum (2020)
The migration flow of Indonesian migrant workers has been touched high numbers from year to year. Malaysia as one of the many destination countries for the placement of Indonesian Migrant Workers, with the most chosen type of work is jobs in the informal sector namely Domestic Workers. The large number of Indonesian domestic workers in Malaysia can cause various problems. Responding to the problems that happened to Indonesian Migrant Workers in Malaysia, the Indonesian government has assigned the Labor Attache to protect all rights of Indonesian Migrant Workers including Domestic Workers. The Labor Attaché as the policy implementer of the central government performs its roles to protect and guarantee the safety of Indonesian Domestic Workers in Malaysia by adjusting the applicable laws. This paper aims to find out the role and efforts of the Labor Attache in protecting Domestic Workers in Malaysia from the problems that happened to them. The framework of thought used in this paper is the theory of Protection Diplomacy, Human Security, and the concept of International Migration. The method that used in this paper is explanatory qualitative research methods, with the process of collecting data through the interviews with related parties and the literature studies. The results of this paper describe that the Labor Attaché has an important roles in protecting Domestic Workers from various problems. And to give a concrete pictures, the author also gives an examples of cases handled by the Labor Attache and the efforts he made in protecting Indonesian Domestic Workers in Malaysia. Keywords: Protection, Indonesian Migrant Workers, Labour Attache, Domestic Workers, Problems.